Evolución del campus universitario. El campus de la UNI 1945-2018 - Ausejo Calmet, Luciana (2025)
In this book, Jairo Espinoza Minaya offers a comprehensive and detailed look at the history of the National University of Engineering (UNI) campus, addressing its transformation from the first buildings to the consolidation of a contemporary and functional university space. Research conducted at the UNI History Center, a center that makes an enormous effort to reconstruct the history of engineering, architecture, and science in Peru, not only documents the architectural evolution of the campus but also contextualizes its development within the framework of the need to create a technical school and the urbanization of Lima during the 20th and 21st centuries. This publication is extremely valuable, as it allows a better understanding of the university city paradigm, providing the community with fundamental tools to understand the configuration of these spaces.